The Portuguese empire in Asia, 1500-1700 a political and economic history - Subrahmanyam, Sanjay (John Wiley & Sons, 2012)
Featuring updates and revisions that reflect recent historiography, this new edition of The Portuguese Empire in Asia 1500-1700 presents a comprehensive overview of Portuguese imperial history that considers Asian and European perspectives